Simulation Game, A Strategy for Achieving Technology Education in Nigerian Secondary Schools - Umeh, Ann E (Advances in Social Sciences Research Journal, 2015)
Simulation game is a concentrated learning exercise specifically designed to represent important real-life activities by providing the learner(s) with the essence or essential elements of the real situation without its hazards, lost or time constraints. Games are contests based on skill and or chance that are played according to rules. The study investigated the effects of simulation game as a strategy for achieving technology education in the Nigerian Secondary Schools. It was an experimental study and use a pre-test treatment control, post-test design. The experimental group was taught Technology instruction with simulation game. Two research questions and two well hypotheses guided the study. One researcher made instrument of 20 item multiple choice questions was used for both pre-test and post-tests. Data collected were analyzed using both mean scores and t-tests. Results showed that gender had no significant effect on the use of simulation game as shown by the performance of the boys and girls. However, the use of simulation game strategy enhances the teaching and learning of Technology Education in the Nigerian Secondary Schools.